2013
DOI: 10.1149/2.114309jes
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cathode and Anode Potentials on the Cycling Performance of Li-Ion Capacitors

Abstract: Li-ion capacitors were assembled with an activated carbon cathode and hard carbon/stabilized lithium metal powder (SLMP) anode. The stabilities of cathode and anode were determined by different methods, including the half-cell and full-cell methods. It was found that the highest potential of the activated carbon electrode should be less than 4.5 V vs. Li/Li+ potential; while the lowest potential of hard carbon/SLMP electrode should be greater than 0.1 V vs. Li/Li+ potential. Scanning electron microscopy images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 16 publications
(10 reference statements)
2
53
1
Order By: Relevance
“…The staging is clearly evident in Fig. 9b in the Gr-SLMP electrode 10 min after introduction of electrolyte, with the gold and red colors evident indicating the LiC 6 and LiC 12 stage co-existence. The presence of different color bands seen at the area around SLMP (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The staging is clearly evident in Fig. 9b in the Gr-SLMP electrode 10 min after introduction of electrolyte, with the gold and red colors evident indicating the LiC 6 and LiC 12 stage co-existence. The presence of different color bands seen at the area around SLMP (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Apart from mitigating the initial cycle loss, pre-lithiation also improves the working potential of the device by providing a lower redox potential to the carbon anode, hence raising the overall cell potential, which further results into higher cell energy density, cycle stability and reduced electrode resistance. 2,6 Moreover, due to the pre-lithiation process, the anion-cation concentration in the electrolyte remains mostly stable during cycling, hence maintaining a steady electrolyte conductivity, which is crucial for cell efficiency and cyclability.Pre-lithiation can be achieved through several methods, 7 including electrochemically driven lithiation, 8 lithiation using external short, lithiation by use of a back-side sacrificial Li, lithiation through composite cathode, 9 lithiation from highly concentrated electrolyte 10 or by * Electrochemical Society Student Member. * * Electrochemical Society Member.…”
mentioning
confidence: 99%
“…112,113 The highest potential of the AC electrode should be lower than 4.5 V vs Li + /Li, while the lowest potential of the HC/stabilized Li metal powder (SLMP) electrode should be greater than 0.1 V vs. Li + /Li. Moreover, the capacitance degradation of this LIC was less than 1 % after 1300 cycles in a voltage range of 2.0 to 4.1 V. 114 Please do not adjust margins Please do not adjust margins Additionally, it was proposed to use quaternary alkyl ammonium and PC based organic electrolytes in LICs. The result showed that the sizes of quaternary alkyl ammonium cations played a very important role in the performance of LICs.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…All the EIS were fitted by the electric equivalent circuit model as shown in Fig. 6(b) [41,42]. Table 3 listed fitting parameters for the LIC150 and LIC300.…”
Section: Samplementioning
confidence: 99%